Emilio González López, Galicia, su alma y su cultura. Ediciones Galicia del Centro Gallego, Buenos Aires, 1954; 217 pp. - Martínez López, Ramón (El Colegio de México, 1956)
Se reseñó el libro: Galicia, su alma y su cultura.